HUBUNGAN ANTARA DAYA TAHAN JANTUNG DAN PARU-PARU DENGAN PRESTASI AKADEMIK PADA SISWA KELAS VIII SMP NEGERI 1 TARIK TAHUN AJARAN 2012-2013 - EKO SUGIANTO, BAGUS (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract  Physical education, sport and health in schools generally prioritize on the basic, including motor skills. Physical education, sport and health not only affects the physic of students, it also covers non - physical areas, such as helping improve the intellectual, the process of socialization in school, family and community; cognitive ( knowledge ) and affective ( attitude ) . To support the students in the school, it takes a good physical fitness. Physical fitness is the ability to perform daily activities with full vitality and alertness without experiencing significant fatigue. With increasing physical fitness and health is expected that students will be better in other subjects receive. This research aim to find out correlation between endurance of heart and lungs and the academic achievement on eighth grade student of SMP Negeri 1 Tarik and to find out how big the role endurance of heart and lungs to their the academic achievement. The type of research is qualitative research with correlational method. Instrument that applied to measure endurance of heart and lungs using MFT and for academic achievement using raport. Data analysis using contingency coefficient. Based on the research result its obtained that student who have very poor VO2 Max status are amounted of 42 students (11 students have poor academic achievement, 19 students have average and 12 have good academic achievement),  meanwhile student who have poor VO2 Max are amounted of 15 students (5 students have average academic achievement, 6 students have a good, and 4 students is very good), student who have good enough VO2 Max is 4 stuents ( 3 students have very good academic achievement and 1 student have the best). Data calculation result using SPSS 20.0 show value result as big as 0.651 and 0.000. it show that sig (0.000) < alpha 0.005, that mean Ho is rejected and H1 is accepted. Thus, from the research result it can be known that endurance of heart and lungs related with academic achievment especially to eighth grade students of SMP Negeri 1 Tarik school year 2012-2013. Keywords : Penjasorkes , Physical Fitness , Academic Achievements